Head and Neck Free Flap Reconstruction in Patients Older than 80 Years - Bhama, Prabhat K.; Patel, Sapna A.; Khan, Umer; Bhrany, Amit D.; Futran, Neal D. (Journal of Reconstructive Microsurgery, 2014)
Background Free tissue transfer is a reliable method for reconstruction of head and neck defects. With the growing number of octogenarians in the population, it is important to understand how these patients respond to these procedures.Methods Through a retrospective chart review of patients who underwent a free-flap reconstruction from 2000 to 2010 at an academic medical center, 48 patients, aged 80 years and older, were compared with a control group consisting of 97 similar patients, aged younger than 80 years. We compared the intensive care unit (ICU) length of stay, overall hospital stay, and the incidence of perioperative complications between the cohorts.Results The average length of stay in the ICU was significantly longer for the octogenarian group as compared with the younger group (101 vs. 41 hours, p-value = 0.007). The average length of hospital stay was not significantly different between the two groups (difference = 40 hours, p-value = 0.102). The incidence of perioperative complication was 75% in the octogenarian group and 60% in the younger group (p-value = 0.095). There were two flap failures in the younger group, and none in the octogenarian group. There was a significantly higher rate of death within 30 days in the octogenarian group.Conclusions Microvascular free tissue transfer is a reliable and safe method of reconstruction of head and neck defects in patients over 80 years of age. Patients should be counseled about the potential risks of increased incidence of medical complications, ICU length of stay, and rate of perioperative death when recommended to undergo free tissue transfer reconstruction.
Keywords: elderly; octogenarian; microvascular reconstruction; free flap; free tissue transfer